PERBANDINGAN PENGGUNAAN MEDIA PERMAINAN DIGITAL INTERAKTIF DALAM PEMBELAJARAN BAHASA INDONESIA - Halimatus Solikah; Anas Ahmadi; Resdianto Permata Raharjo (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This study aims to describe the comparison of the use of interactive digital games in Indonesian language learning. The digital games studied were Quizizz, Wordwall, and Kahoot! This study used a mixed-method research approach with an experimental research design. Research data were obtained using test, interview, and questionnaire techniques. Qualitative research data was obtained through interviews with students and quantitative data was obtained from test results. The quantitative data that has been obtained is then analyzed using N-gain and tested using the one-way ANOVA method. The results showed that there were differences in students' test results between using Quizziz, Wordwall, and Kahoot. Quizizz obtained the highest N-gain value of 0.53, so Quizizz became the most interesting learning media and had a positive impact on students learning Indonesian. The results also show that Quizziz media is the easiest, most convenient, and interesting media to use in learning.